The Influence of Social Media, Influencers, and Destination Attractiveness on Tourist Visits to Tukad Bindu, Kesiman Village, Bali - Anak Agung Istri Agung Maheswari; Ida Ayu Diah Paramitha; Ketut Elly Sutrisni; Ni Putu Yunita Anggreswari (Faculty of Economics and Business, University of Mataram, 2026)
The increasing adoption of digital marketing in tourism has encouraged destinations to utilize social media and influencer marketing as strategic tools to attract visitors. However, previous studies have largely examined the effects of social media, influencers, and destination attractiveness separately, providing limited understanding of how these factors jointly influence tourist visitation behavior, particularly in community-based tourism destinations. Addressing this gap, this study develops an integrated framework based on Digital Marketing Theory, Source Credibility Theory, and Tourism Attraction Theory to analyze the influence of social media, influencers, and destination attractiveness on tourist visits to Tukad Bindu, Kesiman Village, Bali. Using a quantitative survey approach, data were collected from 140 respondents through questionnaires and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results reveal that social media, influencers, and destination attractiveness each have a positive and significant effect on tourist visits, while simultaneously explaining 72.4% of the variation in visitation behavior. Among these variables, destination attractiveness demonstrates the strongest influence on tourists’ decisions to visit. This study contributes to the tourism literature by integrating digital promotion factors and destination attributes into a single analytical model, thereby extending existing knowledge on tourist behavior in community-based tourism contexts. The findings also provide practical implications for destination managers to strengthen social media engagement, establish strategic collaborations with credible influencers, and continuously enhance destination attractiveness to support sustainable growth in tourist visits.